Prevalence and Associated Factors of Intestinal Helminths Among Kindergarten Children in Gondar Town, Northwest Ethiopia - Ayele A; Tegegne Y; Derso A; Eshetu T; Zeleke AJ (Dove Medical Press, 2021)
Abiy Ayele,1 Yalewayker Tegegne,2 Adane Derso,2 Tegegne Eshetu,2 Ayalew Jejaw Zeleke2 1Department of Immunology and Molecular Biology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Medical Parasitology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Adane DersoCollege of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaTel +251930716000Email adanedm77@gmail.comBackground: Intestinal parasitic infections (IPIs) are small organisms that infect the gastro-intestinal tract of human beings. Causes malnutrition, iron deficiency anemia, impairment of physical and mental development in children. The aim of this study was to determine the prevalence of intestinal helminthiasis and associated factors among Kindergarten (KG) children in Gondar Town, northwest Ethiopia.Methods: Institution-based cross-sectional study was conducted on 390 Kindergarten children in Gondar town, Northwest, Ethiopia from March to May 2019. Study subjects were selected using systematic random sampling method. Data were gathered through direct interview by using a pretested questionnaire. Stool specimens were collected and examined using Kato Katz technique. Chi square was used to assess the association between variables and p-value less than 0.05 was taken as a statistical significance.Results: The overall prevalence of intestinal helminthiasis was 16.7%, while those of participants infected by soil-transmitted helminths (STHs) and intestinal Schistosomiasis were 13.8% and 5.9%, respectively. Ascaris lumbricoides was the predominant STHs (9%) followed by Trichuris trichiura (2.3%) and hookworm (1.5%). Light infection was observed in almost all of the infected study participants. Intestinal helminthiasis was found to be significantly associated with age, KG level of children, maternal occupation, and educational status of parents.Conclusion: A significant number of children were infected by intestinal parasites in the study area. A. lumbricoides and intestinal Schistosomiasis were the most predominant of the isolated parasites.Keywords: soil-transmitted helminths, intestinal schistosomiasis, preschool children